Curvature corrections to KPV: do we need deep throats? - Hebecker, Arthur; Schreyer, Simon; Venken, Gerben (Journal of high energy physics, 2022)
We consider α′2 curvature corrections to the action of an NS5-brane which plays the key role in the metastability analysis of warped anti-D3-brane uplifts by Kachru, Pearson and Verlinde (KPV). Such corrections can dramatically alter the KPV analysis. We find that for the α′2-corrections to be sufficiently small to recover essentially the leading-order KPV potential one needs a surprisingly large S3 radius, corresponding to gsM > 20. In the context of the Large Volume Scenario (LVS) this implies a D3-tadpole of at least (103-104). However, large α′2-corrections do not necessarily spoil the uplift in KPV. Rather, as the curvature corrections lower the tension of the brane, a novel uplifting mechanism suggests itself where the smallness of the uplift is achieved by a tuning of curvature corrections. A key underlying assumption is the existence of a dense discretuum of gs. This new mechanism does not require a deep warped throat, thereby sidestepping the main difficulty in uplifting KKLT and LVS. However, all of the above has to be treated as a preliminary exploration of possibilities since, at the moment, not all relevant corrections at the order α′2 are known.
Gesehen am 17.11.2022